Loss analysis on CIGS-modules by using contactless, imaging illuminated lock-in thermography and 2D electrical simulations - Fecher, Frank; Adams, Jens; Vetter, Andreas; Buerhop-Lutz, Claudia; Brabec, Christoph (40th IEEE Photovoltaic Specialist Conference, 2014)
Loss analysis on CIGS-modules are demonstrated by using contactless, imaging illuminated lock-in thermography (ILIT). Power dissipating defects, like shunts, were visualized in commercially manufactured test modules (30 × 30 cm). The evaluations of the ILIT-measurements displayed a correlations with the loss in maximum output power and in open circuit voltage. 2D finite element simulations of the shunts confirmed the correlations. A further simulative parameter study gives a deep understanding of the influence of a shunt on the electrical performance in thin film modules. As ILIT is a contactless and fast method, it has the potential to become a powerful tool for in-line characterization. Furthermore, we consider this technique to be applicable also to other thin film module technologies, like CdTe, a-Si:H or organic photovoltaics.
Keywords: lock-in thermography; module performance; photovoltaic; Pmpp; shunt; Voc